PERSPECTIVES OF PRACTICING MATHEMATICS TEACHERS ON THE SIX STEPS STRATEGY (PETTEC) IN DEVELOPED JORDANIAN CURRICULA - Ghunaimat, Mohammad; Alawneh , Esraa Ahmed (International Online Journal of Education and Teaching, 2025)
The main objective of the study is to know the perceptions of practicing mathematics teachers on using the six steps (PETTEC) in teaching mathematics based on mathematics curricula developed in Jordan, and determining the effect of academic qualification (Non educational qualification, and educational qualification) on the perceptions. The researcher used a descriptive research approach by distributing a questionnaire. The population under investigation consists of all currently employed math teachers who are studying the basic stage math curricula created by the Directorate of Education for the 2023–2024 school year, where there are 179 math teachers. A teacher made up (135) of the study sample that was chosen using the random sample approach. The Finding showed the degree of perceptions of practicing mathematics teachers regarding the six steps strategy (PETTEC) according to the mathematics curricula developed in Jordan is high. Besides, there are no statistically significant differences in perception degree depending on the academic qualification variable for mathematics teachers. The study concluded that mathematics teachers have high perceptions of the six steps strategy (PETTEC) in teaching mathematics. And mathematics teachers provide explanations and all lesson examples, and use the instructions in the teacher's guide.